Mechanics of materials - Gere, James M. (Pacific Grove, CA : Brooks/Cole, 1964)
This book is about: Tension, Compression, and Shear; Axially loaded members; Torsion; Shear forces and bending moments; Stresses in beams; Analysis of stress and strain; Applications of plane stress; ...
Keywords: Strength of materials; Strength of materials